2019
DOI: 10.1039/c8ra09766f
|View full text |Cite
|
Sign up to set email alerts
|

Determining the maximum lanthanum incorporation in the fluorite structure of La-doped ceria nanocubes for enhanced redox ability

Abstract: Ceria nanocubes have been doped with increasing amounts of lanthanum to enhance their redox ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…For low doping levels (x = 0.20), the cube-shaped nanoparticles grow forming larger cubes and consuming the rod-like nanoparticles. This overall comparison indicates that the use of a higher concentration of La nitrate in the synthesis has an effect of retardation in the growth, and similar effects were observed by Loche et al 26…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For low doping levels (x = 0.20), the cube-shaped nanoparticles grow forming larger cubes and consuming the rod-like nanoparticles. This overall comparison indicates that the use of a higher concentration of La nitrate in the synthesis has an effect of retardation in the growth, and similar effects were observed by Loche et al 26…”
Section: Discussionsupporting
confidence: 87%
“…Loche et al achieved 12% of La-doping ceria nanocubes by adding a capping agent. 26 Jiang et al found a mixture of nanocubes and nanorods for Pr 3+ doping higher than 15% without template addition. 27 In the present study, a systematic investigation of ceria nanoparticles doped with lanthanum prepared by the hydrothermal method was performed.…”
Section: Introductionmentioning
confidence: 99%
“…From these characterization techniques, the cubic shape and d -spacing confirm the material authenticity, homogeneous distribution of La, and amounts of La. 100 …”
Section: Characterization Techniquesmentioning
confidence: 57%
“…The obtained %Ce 3+ were 7.8% and 12.9% for the reference SDC and the tested area, respectively. Several studies showed that lanthanum incorporation into the ceria structure promotes the reduction of Ce 4+ into Ce 3+ [55,56]. Thus, the higher concentration of Ce 3+ in the tested area can be attributed to lanthanum incorporation into the ceria structure.…”
Section: Structural and Surface Chemistry Analysismentioning
confidence: 96%